Passages and Afterworlds : Anthropological Perspectives on Death in the Caribbean - Hume, Yanique; Forde, Maarit, 1973- (Book collections on Project MUSE., 2018)
The contributors to this book explore death and its rituals across the Caribbean, drawing on ethnographic theories shaped by a deep understanding of the region's long history of violent encounters, exploitation, and cultural diversity. Examining the relationship between living bodies and the spirits of the dead, the contributors investigate the changes in cosmologies and rituals in the cultural sphere of death in relation to political developments, state violence, legislation, policing, and identity politics. contributors address topics that range from the ever-evolving role of divinized spirits in Haiti and the contemporary mortuary practice of Indo-Trinidadians to funerary ceremonies in rural Jamaica and ancestor cults in Maroon culture in Suriname. Questions of alterity, difference, and hierarchy underlie these discussions of how racial, cultural, and class differences have been deployed in ritual practice and how such rituals have been governed in the colonial and postcolonial Caribbean.